1999
DOI: 10.1111/j.1365-2621.1999.tb15866.x
|View full text |Cite
|
Sign up to set email alerts
|

Flocculation of Whey Protein Stabilized Emulsions as Influenced by Dextran Sulfate and Electrolyte

Abstract: The creaming stability and viscosity of oil-in-water emulsions stabilized by whey protein isolate were monitored as functions of dextran sulfate (DS) and electrolyte (NaCl) concentration. At a specific DS concentration (the critical flocculation concentration, CFC), the droplets became flocculated, which promoted creaming. Addition of electrolyte caused an increase in CFC. At NaCl concentrations Ͻ0.5 wt%, addition of electrolyte decreased emulsion viscosity, but at concentrations Ͼ0.5 wt% it caused an increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…The intrinsic viscosity of this sample of dextran sulfate prepared in aqueous solvent with 0.28 wt % of NaCl was found to be equal to 2.2 ± 0.2 dL g À1 . This result was in accordance with data reported by Demetriades and McClements (1999).…”
Section: Raw Materialssupporting
confidence: 96%
See 2 more Smart Citations
“…The intrinsic viscosity of this sample of dextran sulfate prepared in aqueous solvent with 0.28 wt % of NaCl was found to be equal to 2.2 ± 0.2 dL g À1 . This result was in accordance with data reported by Demetriades and McClements (1999).…”
Section: Raw Materialssupporting
confidence: 96%
“…They did not interact with dextran sulfate, they repelled each other and induced sufficient highly-repulsive forces to overcome the attractive force that could be induced by the steric-exclusive osmotic depletion forces of DS. Moreover, it was reported that the increase in NaCl concentration reduced the degrees of depletion and Van der Waals attractions (Demetriades & McClements, 1999). In good agreement with these results, an increase in NaCl to 0.78wt % reduces by two times the intrinsic viscosity of dextran sulfate.…”
Section: Behavior Of Whey-protein-stabilized Emulsionsupporting
confidence: 63%
See 1 more Smart Citation
“…Thus, the strengthening of the structure takes place probably due to a thickening of the continuous phase as the kefiran concentration is increased. However, the presence of the polysaccharide might also induce a depletion process promoting protein aggregates interactions (Demetriades & McClements, 2006). The presence of a certain amount of polysaccharide in an emulsion system may cause depletion flocculation (Dickinson, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Creaming index. The creaming index, a measure of emulsion stability, was assessed according to the method of Demetriades and McClements (1999). For these experiments, 10 mL volume of each emulsion were delivered into a 15-mL marked tube and stored for the specified time intervals at ambient temperature.…”
Section: Hydration Of Whey Protein (Cwpc Mwpc) Dispersionsmentioning
confidence: 99%